Pengaruh Electronic Word of Mouth (eWOM) terhadap Brand Attitude dan Purchase Intention pada Produk Scarlett Whitening - Rustianingsih, Septi; Setyawan, Anton Agus (Jurnal Maksipreneur, 2025)
Social media has transformed the way conventional marketing operates and introduced a new form of digital marketing, known as Electronic Word of Mouth (eWOM). eWOM plays an important role in consumer purchasing decisions. The purpose of this study is to help businesspeople understand the benefits of eWOM in marketing efforts and to analyze the effect of eWOM generated by users through social media on brand attitudes and purchase intentions for Scarlett Whitening products. The population raised is male and female respondents who know Scarlett whitening products and have seen posts on social media about Scarlett whitening products. The non-probability sampling technique will be the sampling method. Sampling with a purposive type. In this study, a sample of 250 respondents met the research criteria, and the PLS SEM test tool in Smart PLS 3.0 software was used to process the data. The results of this study show that eWOM has a significant positive impact on Brand Attitude, eWOM has a significant positive impact on Purchase Intention, and Brand Attitude has a significant positive impact on Purchase Intention.